2018
DOI: 10.1002/sres.2517
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Dynamic Complexity of Chronic Disease Care in Singapore: Using Group Model Building in Knowledge Elicitation

Abstract: This study describes a group model building exercise that aims to develop a deeper understanding of the dynamic complexity of chronic disease care delivery within a primary care setting in Singapore, leveraging on the insights of stakeholders with personal and institutional knowledge of the health care system. A group model building exercise, which included 50 stakeholders, was used to develop the qualitative model. The qualitative model helped to bring a feedback perspective to understanding the dynamic compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…System dynamics is particularly suited to the study of complex health issues and systems and has been previously used to research matters such as health care capacity and delivery [47] and health system resilience [48]. In regards to questions specifically associated with NCDs, this study complements recent system dynamics analyses reported in the United States [49,50], Singapore [51] and Sierra Leone [52].…”
Section: Discussionmentioning
confidence: 90%
“…System dynamics is particularly suited to the study of complex health issues and systems and has been previously used to research matters such as health care capacity and delivery [47] and health system resilience [48]. In regards to questions specifically associated with NCDs, this study complements recent system dynamics analyses reported in the United States [49,50], Singapore [51] and Sierra Leone [52].…”
Section: Discussionmentioning
confidence: 90%
“…Qualitative system dynamics focuses on the use of causal hypothesis generation tools, such as causal loop diagram, to articulate and visualize our understanding of the complex relationships, dynamics, and interconnectedness between interacting variables that are affecting or are affected by the issue of interest. Meanwhile, quantitative system dynamics models consist of interacting sets of differential and algebraic equations developed from the translation of the qualitative causal loop diagram to a quantitative stock and flow model from a broad range of relevant empirical data to capture dynamic interrelationship [34][35][36]. The systems modelling approach has been used to analyze various oral health problems, including modelling oral healthcare service system in the Netherlands [37], participation in oral health promotion in New York [38] and caries reductions and cost savings from early childhood caries intervention in the United States [39,40].…”
Section: Methodsmentioning
confidence: 99%
“…SD is a computer-facilitated approach to policy analysis and design with a focus on modeling stocks (accumulations) and flows (rates) of systems. Typically, SD is applied to dynamic problems that are characterized by interdependence and mutual interaction of elements, information feedback, and circular causality [ 29 , 30 ]. Virtual worlds, i.e., simulation models, created with SD can act as learning laboratories with the purpose of developing and testing strategies before they are implemented in practice.…”
Section: Study Settingmentioning
confidence: 99%